(untitled) (Journal for the Study of Religion and History (JSRH), 2025)
Through an analysis of a series of letters written by Marc de Rotz, a missionary from the Paris Foreign Missions Society (MEP) in Nagasaki, to Jean-Baptiste Martinet, the Society’s procurator in Shanghai, this study reveals the crucial role of the Shanghai Procure as a central hub in the Catholic missionary network in East Asia during the late nineteenth century. In the circulation system of the MEP’s Eurasian routes at the time, Shanghai was a vital gateway connecting Japan with the headquarters in Paris, thus forming a close link between Shanghai and Nagasaki. The letters show that in the face of challenges, De Rotz turned to Shanghai for theological guidance, material support, and assistance with personal needs. He consulted with the Jesuit priest Aloysius Sica in Shanghai, through the procurator Martinet, on how to handle the issue of traditional beliefs in Japan, which were similar to those in China. He requested prints from the Tushanwan Orphanage by Adolphe Vasseur to be replicated and disseminated in Japan. Additionally, with Martinet’s help, he was able to withdraw funds he had raised in Europe from his Shanghai bank account to alleviate a famine in Sotome. The friendship between De Rotz and Martinet further facilitated the exchange of information and resources between them. This research emphasizes the lasting impact of the Shanghai Procure as a maritime link in the broader network of East-West exchange.